IMPLEMENTASI KEBIJAKAN MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) DI ERA OTONOMI DAERAH SMKN I KUALA CENAKU KABUPATEN INDRAGIRI HULU: (Implementation of School-Based Quality Improvement Management (MPMBS) in the Era of Regional Autonomy SMKN I Kuala Cenaku Kabupaten INHU) - Sri Herawati (UIR Press, 2016)
One issue that is important adult education reform is decentralization of educationmanagement. To implement policies Based Quality Improvement Management School(MPMBS) as an alternative form chosen in the implementation of the decentralization ofeducation, readiness areas and educational institutions (schools) are still in doubt, because toimplement the necessary requirements to be met, especially with regard to human resources,school and community environments. The general objective of this research is that it canprovide a deeper understanding on matters relating to the implementation of policies toimprove the quality of education in the era of decentralization and regional autonomy. WhileSpecifically, this study aims to describe, analyze, and interpret the readiness of resources inSMKN I Kuala Cenaku Desa Kuala Cenaku Inhu in implementing MPMBS, process of policyimplementation MPMBS in SMKN I Kuala Cenaku Desa Kuala Cenaku Inhu, Communityinvolvement in implementation MPMBS policy, factors that support and hinder theimplementation of the policy I MPMBS at SMK Kuala Cenaku Desa Kuala Cenaku Inhu. Theresults of this study indicated that the readiness of human resources (principals and teachers)in Kuala Cenaku SMKN I Desa Kuala Cenaku Inhu in implementing MPMBS policies, inquantity sufficient and ready because they had met the eligibility requirements of the standardof teaching. And also the implementation of policies MPMBS can be quite effective, and canpromise that this program is better than management models and lessons learned in the pasttend to be conventional for involvement or participation in education, especially at theimplementation MPMBS in SMKN I Kuala Cenaku Desa Kuala Cenaku Indragiri Hulu hasincreased.